The complete mitochondrial genome of the horned lizard Phrynosoma blainvillii (Squamata: Phrynosomatidae) from California, USA. Issue 2 (12th December 2017) - Ayala, Laura; Boo, Ga Hun; Boo, Sung Min; Cluff, Brandon; Dayton, Gage H.; Edwards, Leah; Garcia, Armando; Gomez, Mariana; Jimenez, Thomas A.; Hughey, Jeffery R.; Huynh, Timothy; Marquez, Natalia I.; et al.
Abstract: Analysis of Phrynosoma blainvillii Gray from Marina, Monterey County, California, using 150 bp paired-end Illumina sequences (Illumina, San Diego, CA) resulted in the assembly of its complete mitogenome. The mitogenome is 16, 946 bp in length and contains a putative origin of light strand replication (OL), control region, 22 tRNA, 2 rRNA, and 13 protein-coding genes. Its content and organization are similar to other Squamata. Phylogenetic analysis of P. blainvillii resolves it in a clade with P. sherbrookei Nieto-Montes de Oca, Arenas-Moreno, Beltrán-Sánchez & Leaché, sister in position to Uma notata Baird. Mitochondrial marker analysis of P. blainvillii from Marina shows that it belongs to a coastal Santa Lucia Mountain Range haplogroup that is distinct from other populations of P. blainvillii in California.